2021
DOI: 10.1021/acsomega.1c05297
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of IL-6 by Hypochlorous Acids: Effects on Receptor Binding

Abstract: Interleukin-6 (IL-6) has been implicated in the pathogenesis of inflammatory events including those seen with COVID-19 patients. Positive clinical responses to monoclonal antibodies directed against IL-6 receptors (IL-6Rs) suggest that interference with IL-6-dependent activation of pro-inflammatory pathways offers a useful approach to therapy. We exposed IL-6 to hypochlorous acid (HOCl) in vitro at concentrations reported to develop in vivo . After HOCl treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In that sense, and according to the findings in the animal model of this study, the administration of NES was beneficial in modulating IL-6 levels, which correlated with a reduction in joint damage, especially for the group treated with the highest dose of NES (NES40). Furthermore, a recent in vitro report showed that hypochlorous acid (HOCl), one of the main components of NES, is capable of interacting with IL-6, blocking or reducing interaction with its receptors in a dose-dependent manner [ 29 ], although more studies are needed in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, and according to the findings in the animal model of this study, the administration of NES was beneficial in modulating IL-6 levels, which correlated with a reduction in joint damage, especially for the group treated with the highest dose of NES (NES40). Furthermore, a recent in vitro report showed that hypochlorous acid (HOCl), one of the main components of NES, is capable of interacting with IL-6, blocking or reducing interaction with its receptors in a dose-dependent manner [ 29 ], although more studies are needed in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…By inactivating interleukin 6 (IL6), HOCl possibly downregulates mediators of the ‘cytokine storm’ that characterizes clinical deterioration in specific diseases (e.g., COVID-19) [ 48 ], [ 52 ], [ 53 ]. Based on their in vitro studies on the deactivation of IL-6 by HOCl at concentrations reported to develop in vivo , Robins et al [ 54 ] suggest that exogenous HOCl and NCT might bring about beneficial effects in the treatment of COVID-19. Their results and further studies on how HOCl and HOBr and their halogenated amine derivates interact with IL-6 may open alternative therapeutic interventions in COVID-19 and other hyperinflammatory diseases.…”
Section: Hocl – a Natural Biocidementioning
confidence: 99%
“…IL-6, IKK) and mediators of tissue remodeling (e.g. MMP7, TIMP-1), causing effects that are mostly consistent with modulation, attenuation, and resolution of inflammatory tissue responses (35,(80)(81)(82)(83)(84)(85)(86)(87)(88)(89). Specifically, inactivation of IKK (inhibitor of IkB kinase) through oxidation (Cys114/115) is thought to cause the hypochlorite-dependent attenuation of psoriasis observable upon topical application (35).…”
Section: Biomolecular Targets Of Chlorination Stress: From Chemical M...mentioning
confidence: 99%
“…Importantly, N-chlorotaurine formation may cause the negative regulation of inflammatory processes by multiple distinct molecular mechanisms attenuating NF-kB and related cytokine signaling (88,116). Interestingly, taurine might not only attenuate direct chemical reactivity of HOCl through sacrificial quenching, but chloro-taurine may then act as a redox-directed signaling modulator of major inflammatory targets and pathways.…”
Section: Endogenous Phytochemical and Synthetic Hocl-antagonists: Ant...mentioning
confidence: 99%
See 1 more Smart Citation